2010
DOI: 10.1002/ejoc.201000642
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Synthesis of the Epoxyquinol (+)‐Isoepiepoformin

Abstract: The epoxyquinol natural product (+)‐isoepiepoformin (1) has been synthesized for the first time and in an unambiguous fashion by using the scalemic cis‐1,2‐dihydrocatechol 2 as starting material. The spectroscopic data derived from the synthetic sample of compound 1 match those reported in the literature for the natural product and thereby confirm the structure assigned to the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The relative configuration of 2 was established as 2,3- cis /3,4- cis by comparing the J 2,3 (2.6 Hz) and J 3,4 (4.1 Hz) coupling values with coupling constants for other cyclohexanone oxides ( Table S1 ). 15 29 This conclusion was also supported by ROESY correlations between H-2 and H-3 and between H-3 and H-4 (Figure 2 ). DFT calculations (ECD and specific rotation) were performed to determine the absolute configuration of 2 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The relative configuration of 2 was established as 2,3- cis /3,4- cis by comparing the J 2,3 (2.6 Hz) and J 3,4 (4.1 Hz) coupling values with coupling constants for other cyclohexanone oxides ( Table S1 ). 15 29 This conclusion was also supported by ROESY correlations between H-2 and H-3 and between H-3 and H-4 (Figure 2 ). DFT calculations (ECD and specific rotation) were performed to determine the absolute configuration of 2 .…”
Section: Resultssupporting
confidence: 68%
“…The small J 2,3 (3.8 Hz) and J 3,4 (2.1 Hz) coupling constant values supported a 2,3- cis /3,4- cis relative configuration based on comparisons of these data with those for other similarly substituted cyclohexanones (Table S1). The ROESY correlations between H-2 and OH-3, H-4 and OH-3, and H-3 and OH-2, as well as the NOE enhancement of H-2 and H-4 upon irradiation of H-3, supported the presence of two interchangeable half-chair conformations, 1a and 1b , as shown in Figure . In order to determine the absolute configuration of 1 , a lowest energy conformation search was carried out in Spartan’10 using the proposed configuration 2 S ,3 S ,4 S .…”
Section: Resultsmentioning
confidence: 79%
“…One of the advantages of this biocatalytic process is that single biotransformations can be readily scaled up to produce large quantities (multi-grams to kilograms) of enantiopure cis-dihydrodiols 1 (e.g., R = F, Cl, Br, I). Although, a small number of cis-dihydrodiols 1 has been extensively used in the synthesis of natural products, [2][3][4] to date, their full potential in the synthesis of chiral ligands has not been realised. The current feasibility study has been carried out in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Among the natural compounds, only the structure of gabosine N, (4R,5R,6R)-4,5,6-trihydroxy-2-methylcyclohex-2-enone (Tang et al 2000), has been reported. The remaining hits were mainly derivatives of other gabosines different from H or derivatives such as 5-hydroxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one (White et al, 2010), which is an epoxide with different configuration of the asymmetric carbons compared with gabosine H.…”
Section: Database Surveymentioning
confidence: 99%